Sovereign Defaults : The Role of Volatility - Sutton, Bennett; Catao, Luis. (Washington, D.C. : International Monetary Fund, 2002)
While the relationship between volatility and credit risk is central to much of the literature on finance and banking, it has been largely neglected in empirical macro studies on sovereign defaults. This paper presents new econometric estimates for a panel of 25 emerging market countries over 1970-2001, breaking down aggregate volatility into its external and domestic policy components. We find that countries with historically higher macroeconomic volatility are more prone to default, and particularly so if part of this volatility is policy-induced. Reducing policy volatility thus appears to be key to improving a country's credit standing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet